On the electric propulsion of rive ships - Aurel-Dan Maimon (Annals of "Dunărea de Jos" University of Galaţi: Fascicle XI Shipbuilding)
Electric propulsion for river ships is an exciting and promising development in the maritime industry. This technology involves using electric motors powered by batteries instead of traditional internal combustion engines. Advances in battery technology, such as lithium ion batteries, have made electric propulsion more viable and cost-effective. It is generally more efficient than internal combustion engines, leading to a better fuel economy and lower operational costs and it produces significantly less pollution compared to traditional engines, which burn heavy oil. This helps reduce greenhouse gas emissions and other pollutants like NOx and particulate matter. In plus, electric motors are quieter than traditional engines, making electric ships more suitable for operations in urban areas and sensitive environments. There are also some ships using hybrid systems that combine electric propulsion with traditional engines, allowing them to switch between power sources depending on the situation.